Perancangan Bisnis untuk Produk Natural Personal Care "Bathe" - Michelle Pricillia Wijaya; Rendy Iswanto (Jurnal Vicidi, 2018)
Nowadays, there are so many soap and lotion brand with various price and variations in the market. But, people do not know that the products they used containing bad chemicals either for their skin or enviroment. In this research, author wants to develop for Bathe products in order to know more about people’s awareness about natural products and best business strategic for Bathe. This journal is supported by using field data (primary) and literature (secondary). The products development process has done through several stages starting from observation, interview, and online survey. The results are people still did not know about the ingredients of the product they used everyday, why people have to change to natural products, and people’s visual preferences and variations.